A rare case of signet ring cell carcinoma of the appendix. Issue 7 (14th July 2020) - Caesar-Peterson, Shannon; Tulla, Katrina; Southall, Colton; Lin, Ying; Genelus-Dominique, Elvita
Abstract: Primary appendiceal carcinoma itself comprises less than 0.5% of all gastrointestinal malignant neoplasms. However, signet ring cell carcinoma of the appendix is an extremely rare subset of primary appendiceal carcinomas. This sub-type of appendiceal carcinoma represents only 4% of all appendiceal carcinomas. In this case report, we present a case of signet ring cell carcinoma found in a 65-year-old male patient which presented as acute appendicitis. He was diagnosed after a laparoscopic appendectomy by histopathological evaluation.